2021
DOI: 10.1016/j.jseint.2020.12.018
|View full text |Cite
|
Sign up to set email alerts
|

An integrated educational and multimodal approach to achieving an opioid-free postoperative course after arthroscopic rotator cuff repair

Abstract: Background In the realm of shoulder surgery, arthroscopic rotator cuff repair (RCR) is one of the most painful procedures and is often associated with higher opioid consumption. The purpose of this study was to evaluate effectiveness of preoperative and postoperative patient education and multimodal pain management to achieve an opioid-free postoperative recovery after RCR. Methods Sixty patients who underwent RCR were divided in 2 groups. All patientsreceived an inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition, the study showed that among patients undergoing shoulder arthroplasty 100% of those who received preoperative, intraoperative, and postoperative patient education in addition to multimodal pain management were opioid free by 2 weeks. 54 , 62 Brown-Taylor et al reported that 8 studies concluded a relationship between early PT and reduced subsequent opioid use in orthopedic procedures. 3 , 9 , 55 Therefore, these variables may be valuable areas to examine in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the study showed that among patients undergoing shoulder arthroplasty 100% of those who received preoperative, intraoperative, and postoperative patient education in addition to multimodal pain management were opioid free by 2 weeks. 54 , 62 Brown-Taylor et al reported that 8 studies concluded a relationship between early PT and reduced subsequent opioid use in orthopedic procedures. 3 , 9 , 55 Therefore, these variables may be valuable areas to examine in future studies.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 16 , 30 , 38 , 48 , 60 Most orthopedic surgeons agree that overprescription is a problem, and significant efforts have been made to reduce opioid prescribing practices including the investigation and development of multimodal pain-management protocols and patient education tools. 23 , 31 , 35 , 44 , 53 , 54 However, the use of narcotics for postoperative pain control still remains frequent, particularly following shoulder surgeries. 30 , 60 , 67 Given the persistent challenge of the opioid crisis and the rapidly increasing utilization of shoulder surgery, there is a growing need for tools to identify patients at risk of chronic use, abuse, and dependence.…”
mentioning
confidence: 99%
“…42 Several pain protocols are now available for nearly every orthopaedic subspecialty. [43][44][45][46][47] The most common components include NSAIDs, non-narcotic analgesics, local and regional anesthetics, cold therapy, and stress relievers. Opioids are often included for the first few days, with a transitional emphasis to nonopioids to prevent long-term use.…”
Section: Educationmentioning
confidence: 99%